Cross sections of the 3H(d, t)np reaction at the 37 MeV deuteron beam energy - O. O. Beljuskina; V. I. Grantsev; K. K. Kisurin; S. E. Omelchuk; J. S. Roznjuk; B. A. Rudenko; L. I. Sljusarenko; B. G. Struzhko (Âderna Fìzika ta Energetika, 2014)
Inclusive 3H spectra and differential cross sections of the 3H(d, t) reaction are measured at the deu-teron beam energy of 36,9 MeV. Shapes of the inclusive 3H spectra were reproduced by using a model that takes into account simple quasi-binary mechanisms and characteristics of the experimental method, i.e., nonmono-chromaticity of the accelerated deuteron beam, target thickness, spectrometer energy resolution, beam spot size on the target, detector apertures, and target–detector distance. It is found that the most important processes in the 3H(d, t) reaction are the proton-neutron Final State Interactions in the singlet 1S0 state (singlet deuteron) and in the triplet 3S1 one, sequential decay via the 4H* resonance (Ent = 2,2 MeV, Г = 3,4 MeV) and the proton (neutron) - triton quasifree scattering processes.